Associations between dietary patterns and the metabolic syndrome in older adults in New Zealand: the REACH study. Issue 9 (14th November 2022) - Mumme, Karen D.; Conlon, Cathryn; von Hurst, Pamela R.; Jones, Beatrix; de Seymour, Jamie V.; Stonehouse, Welma; Heath, Anne-Louise; Coad, Jane; Haskell-Ramsay, Crystal F.; Mugridge, Owen; Slade, Cassandra; Beck, Kathryn L.
Abstract: The metabolic syndrome is common in older adults and may be modified by the diet. The aim of this study was to examine associations between a posteriori dietary patterns and the metabolic syndrome in an older New Zealand population. The REACH study (Researching Eating, Activity, and Cognitive Health) included 366 participants (aged 65–74 years, 36 % male) living independently in Auckland, New Zealand. Dietary data were collected using a 109-item FFQ with demonstrated validity and reproducibility for assessing dietary patterns using principal component analysis. The metabolic syndrome was defined by the National Cholesterol Education Program Adult Treatment Panel III. Associations between dietary patterns and the metabolic syndrome, adjusted for age, sex, index of multiple deprivation, physical activity, and energy intake were analysed using logistic regression analysis. Three dietary patterns explained 18 % of dietary intake variation – 'Mediterranean style' (salad/leafy cruciferous/other vegetables, avocados/olives, alliums, nuts/seeds, shellfish and white/oily fish, berries), 'prudent' (dried/fresh/frozen legumes, soya-based foods, whole grains and carrots) and 'Western' (processed meat/fish, sauces/condiments, cakes/biscuits/puddings and meat pies/hot chips). No associations were seen between 'Mediterranean style' (OR = 0·75 (95 % CI 0·53, 1·06), P = 0·11) or 'prudent' (OR = 1·17 (95 % CI 0·83, 1·59), P = 0·35) patterns and the metabolic syndrome after co-variate adjustment. The 'Western' pattern was positively associated with the metabolic syndrome (OR = 1·67 (95 % CI 1·08, 2·63), P = 0·02). There was also a small association between an index of multiple deprivation (OR = 1·04 (95 % CI 1·02, 1·06), P < 0·001) and the metabolic syndrome. This cross-sectional study provides further support for a Western dietary pattern being a risk factor for the metabolic syndrome in an older population.